Copyright Protection in the Adaptation of Foreign Films into Indonesian Films - Ellora Sukardi; Khairiyah Hanan Rafidah (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2025)
The increasing trend of Indonesian films adapted from foreign works highlights the growing interaction between local creative industries and global cultural flows. However, this development raises significant legal issues, particularly regarding copyright protection, licensing mechanisms, and compliance with international standards. This study examines the legal framework governing copyright protection in the adaptation of foreign films into Indonesian films by analyzing national regulations, primarily Law Number 28 of 2014 on Copyright and Law Number 33 of 2009 on Film, and relevant international instruments, including the Berne Convention and the TRIPs Agreement. Using a normative juridical method with statutory, conceptual, and comparative approaches, this research evaluates how adaptation rights, moral rights, and licensing obligations are implemented in practice. The findings indicate that although Indonesian law provides a clear basis for regulating adaptation, challenges persist, such as insufficient licensing compliance, weak enforcement, and limited legal literacy among industry practitioners. These obstacles contribute to the recurring risks of infringement and contractual disputes. The study concludes that strengthening copyright governance, improving licensing transparency, and enhancing cross-border enforcement mechanisms are essential to ensuring lawful and ethical film adaptations in Indonesia.